'Antique Fiction' and the forgotten legacies of ancient Rome in Wilkie Collins's Antonina. (18th April 2016) - Eastlake, Laura
Abstract : This article examines the treatment and uses of ancient Rome in Wilkie Collins's first published novel, Antonina (1850). It suggests that the novel, which has been almost entirely overlooked by modern scholarship, represents a significant departure from earlier, more negative receptions of Rome in the cultural and political discourses of the early nineteenth century, as well as in the 'antique fictions' of the period. Rather, Antonina represents a shift towards a more enthusiastic adoption of the Roman past as a framework for glorifying the racial and cultural credentials of the British imperialist. Set during the sack of Rome by Alaric and the Goths in 410, the novel's romantic pairing of the Roman maiden Antonina and the Gothic warrior Hermanric serves to mythologize the origins of a British readership who would be heirs to Roman culture and empire as well as Gothic martial virtue.